Fluks Poynting Gelombang Whistler - Titiek Setiawati (Institut Teknologi Bandung, 2002)
The whistler wave which exists in the ionosphere and magnetosphere spans in the VLF and ELF. During its propagation the wave can undergo an attenuation. The attenuation that is represented as Poynting flux is derived from the electric and magnetic fields components along with their conjugate components. Poynting flux profile in the lower ionosphere (D layer) can be simulated by using the modification of the full wave method.